Enhancing Learners’ Speaking Ability in Project-Based Learning (PjBL):How does the Inside-Outside Circle Technic Work? - I Made Rai Jaya Widanta (Universitas Pendidikan Ganesha, 2023)
Project-based learning has been widely recommended in the era of Merdeka Belajar Kampus Merdeka to facilitate learners with the natural, authentic, and meaningful English learning. In its implementation, PjBL also ruins hinderance for learners are frequently not ready with language treasure especially spiking skill to execute the project. This article is aimed to analyze how learners’ speaking skill was enhanced to embody learners’ readiness prior to the project execution. The research participants were sixty semester, two students majoring in mechanical engineering who have been having English for description subject. The subject has been given during the semester which implement PjBL model. The data were collected by observational technic and focused-group discussion. Upon the data were collected, the data were analysed and reported with narration. The results show that inside-outside circle strategy merely helped provide them chances to practice speaking and other ability using project-related language topics. Evaluation result through observation and focused group discussion revealed that students were able to improve their language skill, motivation and self-confidence for the project.